The Efficiency of Public Procurement in the Republic of Kosovo: an Econometric Approach - Kacandolli - Gjonbala, Drita; Shiroka - Pula, Justina; Berisha - Shaqiri, Afërdita; Osmani, Myslym (Ekonomika, 2018)
[full article and abstract in English] This study aims at investigating and assessing the efficiency of the public procurement system and its main factors in the Republic of Kosovo. For this purpose, we collect data for a random sample of 243 economic operators (companies) eligible to benefit from public funds. We analyzed the data using descriptive analysis as well as econometric modeling, and we have used classical and ordinal logistic (o-logit) econometric models. In the absence of a direct indicator, the efficiency of procurement is measured by two proxy variables, discrimination- tendering criteria and a favor made to specific companies to win tenders, by their average as a third optional variable. Discrimination and favor are found to be present to a large extent, meaning that efficiency is very low. Among the major factors of the low efficiency of public procurement were political intervention, the non-transparency of the procurement process, a lack of capacity to implement procurement legislation and manage contracts, corruption and insufficient knowledge about procurement. Based on these results, important implications would lie in introducing measures for enhancing transparency, improving legislation, recruiting especially qualified staff or providing continuous training for the current procurement staff as well as improving the motivation of the staff to properly implement legislation and manage the procurement contracts.